Radiofluorination and first radiopharmacological characterization of a SWLAY peptide‐based ligand targeting EphA2. (29th September 2014) - Pretze, Marc; Mosch, Birgit; Bergmann, Ralf; Steinbach, Jörg; Pietzsch, Jens; Mamat, Constantin
<x xml:space="preserve">Abstract</x> Peptides labeled with short‐lived positron emitters are of considerable interest as probes for molecular imaging by positron emission tomography. Herein, the regioselective and convenient radiofluorination of a biologically relevant alkyne‐modified SWLAY peptide bound on solid support with the radiolabeling building block 1‐(3‐azidopropyl)‐4‐(3‐fluoropropyl)piperazine ([18F]AFP) is described. Peptides including this amino acid sequence are promising candidates for imaging of the erythropoietin‐producing hepatoma cell line‐A2 receptor (Eph), which is an interesting target for tumor imaging due to its overexpression in various tumor entities. The desired 18F‐peptide could be prepared in a total synthesis time of 140 min including the removal of the catalytic copper species and was obtained with a radiochemical yield of 11 ± 2% (n = 5) and a radiochemical purity >98%. The method's feasibility for a robust and bioorthogonal radiolabeling via the 1, 3‐dipolar Huisgen cycloaddition was demonstrated. Preliminary radiopharmacological studies regarding the metabolic stability of the peptides in cell culture supernatants and rat plasma were accomplished as well as the cellular association of the 18F‐peptide in erythropoietin‐producing hepatoma cell line‐A2‐overexpressing human melanoma cells in vitro. Furthermore, an initial in vivo positron emission tomography experiment was performed, which showed a fast metabolism of the novel 18F‐peptide.